Measuring change in health-related quality of life: the impact of different analytical methods on the interpretation of treatment effects in glioma patients - Coomans, Marijke; Taphoorn, Martin J B; Aaronson, Neil K; Baumert, Brigitta G; van den Bent, Martin; Bottomley, Andrew; Brandes, Alba A; Chinot, Olivier; Coens, Corneel; Gorlia, Thierry; Herrlinger, Ulrich; Keime-Guibert, Florence; et al. (Neuro-oncology practice, 2020)
Different analytical methods may lead to different conclusions about the impact of treatment on health-related quality of life (HRQoL). This study aimed to examine 3 different methods to evaluate change in HRQoL and to study whether these methods result in different conclusions.HRQoL data from 15 randomized clinical trials were combined (CODAGLIO project). Change in HRQoL scores, measured with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 and BN20 questionnaires, was analyzed in 3 ways: (1) at the group level, comparing mean changes in scale/item scores between treatment arms, (2) at the patient level per scale/item, calculating the percentage of patients that deteriorated, improved, or remained stable per scale/item, and (3) at the individual patient level, combining all scales/items.Baseline and first follow-up HRQoL data were available for 3727 patients. At the group scale/item level, only the item “hair loss” showed a significant and clinically relevant change (ie, ≥10 points) over time, whereas change scores on the other scales/items were statistically significant only (all P < .001; range in change score, 0.1-6.2). Although a large proportion of patients had stable HRQoL over time (range, 27%-84%) on the patient level per scale/item, many patients deteriorated (range, 6%-43%) or improved (range, 8%-32%) on a specific scale/item. At the individual patient level, the majority of patients (86%) showed both deterioration and improvement, whereas only 1% remained stable on all scales.Different analytical methods of changes in HRQoL result in distinct conclusions of treatment effects, all of which may be relevant for informing clinical decision making.